Konfrontatie 2 : 5 Nederlandse - 5 Vlaamse Kunstenaars : aktuele kunst in de lege ruimte. - de lege ruimte, Brugge (Brugge : De Lege Ruimte, 1984)
Coucke, Jo ; Devriendt, Robert ; Kuiper, Ineke ; Sjardijn, Martin ; Slock, Lucy ; Snikkens, Kees ; Vandekerckhove, Hans ; Visser, Mieke ; Werdler, Elly ; Willockx, Andre
Konfrontatie 2 : 5 Nederlandse - 5 Vlaamse Kunstenaars : aktuele kunst in de lege ruimte, Brugge, 30 mei t/m 17 juni 1984
boek